DISPARITAS MEDIA PEMBELAJARAN PADA ERA DIGITALISASI PENDIDIKAN DI WILAYAH PERBATASAN RI-RDTL (REFLEKSI PEMBELAJARAN ONLINE DAERAH PERBATASAN) - Darius Yonatan Nama; FEMBERIANUS SUNARIO TANGGUR (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2022)
The purpose of the study was to determine the disparity in the use of learning media and the barriers to the digitalization of learning media programs in the border areas of Indonesia and RDTL. The research approach is qualitative with descriptive method. Research informants are principals, teachers and students. Data collection techniques using observation, interviews, document studies, questionnaires. The data analysis technique consists of 3 flow of activities carried out simultaneously, namely data reduction, data presentation and conclusion drawing/verification. The result of the research is that from a total of 17 border area schools with a total of 143 teachers, 122 teachers (85%) did not use digital-based learning media, while 21 teachers (15%) used digital-based learning media. The inhibiting factors for the use of digital-based learning media in border areas are, First, the development of technology-based infrastructure that has not been evenly distributed in the RI-RDTL border area. Second, the absence of free internet access for border area communities has an impact on the availability of internet quotas for teachers and students in carrying out online learning activities. Third, the low knowledge of teachers in managing online learning activities such as the use of digital-based learning media.